Nilai Budaya Pendidikan Olahraga “Etu “ Dalam Mendukung Pembelajaran Olahraga di Kabupaten Nagekeo - Ajito, Timoteus; Lodo, Rozita Y.; Mansuetus Mola (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
One of the cultural heritages of the Indonesian nation is the Etu traditional boxing tradition. Besides being loaded with various skills and dexterity for self-defense, Etu's traditional boxing is also to test virility, courage between youths in Nagekeo district who are rich with the traditions that surround them. Etu's traditional boxing sport is very rich in socio-cultural values ​​and philosophical meanings. This study aims to find out: 1) The noble values ​​contained in Etu, 2) Describe the formation of Community Character in Etu sports, 3). Describe Sports Education Activities for Schools. in the Nagekeo district of East Nusa Tenggara, and saw the process of inheriting the Etu traditional boxing sport from generation to generation. This study uses a qualitative approach where data is obtained using Miles Matthew's analysis. B and Huberman Michael, which consists of three stages, namely data reduction, data presentation, and ends with drawing conclusions. The results of the study show that Etu's traditional boxing is not just a sport. Etu's traditional boxing sport is a means to gain movement experience which is useful for growth and development of physical and fitness, mental and courage, in addition to uniting, familiarizing one with another, but full of value and meaning in people's lives. The process of inheriting the traditional Etu boxing tradition has also been going well until now